ANALISIS TINGKAT KEPUASAN KONSUMEN DALAM MENGONSUMSI IKAN LENCAM (Lethrinus ornatus) DI PASAR RUMAHTIGA KECAMATAN TELUK AMBON - Kesya Pattimukay; Janer Sangaji (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2025)
This study aims to analyze consumer satisfaction levels based on a set of service attributes that reflect both product quality and service delivery processes. A total of 30 respondents were selected as the sample using accidental sampling. The respondent characteristics analyzed included gender and age, providing a demographic overview that may influence perceptions of service quality and the resulting satisfaction. Consumer satisfaction was measured using seven verified attributes, namely product quality, price, service, reliability, responsiveness, assurance, and empathy. Descriptive analysis results indicate that most respondents fall into the high-satisfaction category, with a CSI score of 0.80, particularly for product quality, competitive pricing, and service performance. These findings align with previous studies stating that service quality dimensions and value for money are key determinants of satisfaction, loyalty, and repurchase intention. The study provides practical implications for business managers to enhance the consistency of service quality and maintain the attributes that strongly influence consumer satisfaction. Moreover, the findings can serve as a reference for developing service improvement strategies that are more oriented toward consumer needs and preferences